EKTIFITAS HIPNOTERAPI TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA YANG MENGALAMI HIPERTENSI - Lukluul Hidayati (Journal of Holistic and Traditional Medicine, 2020)
The elderly period in years constitute human formative last term. Where does someone experience physical function decrease and social by natures.One of method to settle hypertension with hypnotherapy. This research intent to know influence hypnotherapy to blood pressure change on elderly.Who is experience hypertension at sub-district Pojok Kediri to year 2015.On this research available 16 respondent that accomplish criterion. On all respondent is done pretest to determine phase blood pressure before intervention,here after been given intervention hypnotherapy as much four sessions, in three weeks, each session has given hypnotherapy up to 30 minutes. In the late week to be done post test on all respondent. On this research can that mean's average pretest on all respondent points out high blood pressure. On posttest mean's average on all respondent already being given by intervention points out decrease of high blood pressure become normal (80%). This observational method do by different two mean's statistic quiz paired T test with hypothesis quiz one tail and purpose phase 95 % ( α = 0,05 ). After do examination, gotten by result available distinctive significant afters blood pressure done hypnotherapy the elderly who experiences hypertension. So gets to be concluded that hypnotherapy having for down hypertension patient blood pressure elderly at sub-district to Pojok Kediri. Therefore hypnotherapy can be utilized as therapy of complementary to down hypertension patient blood pressure on elderly. Succeeding research needs than effectiveness hypnotherapy with the other therapy to down hypertension patient blood pressure. The elderly period in years constitute human formative last term. Where does someone experience physical function decrease and social by natures.One of method to settle hypertension with hypnotherapy. This research intent to know influence hypnotherapy to blood pressure change on elderly.Who is experience hypertension at sub-district Pojok Kediri to year 2015.On this research available 16 respondent that accomplish criterion. On all respondent is done pretest to determine phase blood pressure before intervention,here after been given intervention hypnotherapy as much four sessions, in three weeks, each session has given hypnotherapy up to 30 minutes. In the late week to be done post test on all respondent. On this research can that mean's average pretest on all respondent points out high blood pressure. On posttest mean's average on all respondent already being given by intervention points out decrease of high blood pressure become normal (80%). This observational method do by different two mean's statistic quiz paired T test with hypothesis quiz one tail and purpose phase 95 % ( α = 0,05 ). After do examination, gotten by result available distinctive significant afters blood pressure done hypnotherapy the elderly who experiences hypertension. So gets to be concluded that hypnotherapy having for down hypertension patient blood pressure elderly at sub-district to Pojok Kediri. Therefore hypnotherapy can be utilized as therapy of complementary to down hypertension patient blood pressure on elderly. Succeeding research needs than effectiveness hypnotherapy with the other therapy to down hypertension patient blood pressure.